Propaganda for War the Dissemination of the Crusading Ideal in the Twelfth Century - Morris, Colin (Studies in church history, 1983)
It was accepted in western Europe, in the twelfth and thirteenth centuries, that there was an obligation upon the military classes, and indeed on Christians generally, to take up arms in defence of the Holy Sepulchre, or to participate in other expeditions authorised by the ecclesiastical hierarchy. War ceased to be, for Christians, a regrettable necessity, and became a virtue, and armies were summoned by the trumpet-blasts of the Prince of Peace. There has been a great deal of work by historians in recent decades on the transformation of earlier Christian ideology, and we now understand much more about the origins of crusading ideas, the discussion of warfare by theologians and canon lawyers, and the profound changes in spirituality which accompanied the rise of militarism. There is however a technical aspect of the subject which is less often considered: the actual methods by which the new ideals were communicated to western society generally. By any standards, it was a remarkably successful exercise in publicity. It was also, in the first instance, very rapid. Urban II announced the expedition to Jerusalem at the Council of Clermont in November 1095, and he fixed the date of departure as 15 August 1096. The summons was heard by groups far wider than the princes and their households, and by Easter 1096 an army led by Peter the Hermit had already arrived in Cologne on its way from northern France. Within a few months, therefore, and well in advance of the papal deadline, the message had spread to all levels of society over a wide geographical area. A system of communication as effective as this deserves our respect and study. It would be a mistake to conclude from the total absence of modern technology that the control of opinion was unimportant in the twelfth and thirteenth centuries.